14. Recovery: the business case - Slade, Mike; McDaid, David; Shepherd, Geoff; Williams, Sue; Repper, Julie (ImROC, 2017)
This paper makes the Business Case for supporting recovery. We believe that this should be informed by three types of data: evaluative research (such as randomised controlled trials); the perceived benefits for service users – what might be termed ‘customer satisfaction’; and best evidence about value for money.